2009
DOI: 10.1088/0953-8984/21/27/275408
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure phases and transitions of the layered alkaline earth nitridosilicates SrSiN2and BaSiN2

Abstract: We investigate the high-pressure phase diagram of SrSiN 2 and BaSiN 2 with density-functional calculation. Searching a manifold of possible candidate structures, we propose new structural modifications of SrSiN 2 and BaSiN 2 attainable in high-pressure experiments. The monoclinic ground state of SrSiN 2 transforms at 3 GPa into an orthorhombic BaSiN 2 type. At 14 GPa a CaSiN 2 -type structure becomes the most stable configuration of SrSiN 2 . A hitherto unknown Pbcm modification is adopted at 85 GPa and, final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…[25] several hitherto unknown high-pressure polymorphs of MSiN 2 with M = Be, Mg, Ca. [84] The quaternary lithium alkaline earth nitridosilicates Li 2 MSi 2 N 4 with M = Ca, Sr form an established network structure. [85] In this case, the structure is closely related to that of BaAl 2 S 4 , BaGa 2 S 4 , and the high-pressure modifications of the borates MB 2 O 4 (M = Ca, Sr), which are reported to crystallize in Net 39. , they are used industrially in pc-LEDs as highly efficient red-to-orange emitting luminescent materials (see Section 7.5).…”
Section: Tectosilicatesmentioning
confidence: 99%
“…[25] several hitherto unknown high-pressure polymorphs of MSiN 2 with M = Be, Mg, Ca. [84] The quaternary lithium alkaline earth nitridosilicates Li 2 MSi 2 N 4 with M = Ca, Sr form an established network structure. [85] In this case, the structure is closely related to that of BaAl 2 S 4 , BaGa 2 S 4 , and the high-pressure modifications of the borates MB 2 O 4 (M = Ca, Sr), which are reported to crystallize in Net 39. , they are used industrially in pc-LEDs as highly efficient red-to-orange emitting luminescent materials (see Section 7.5).…”
Section: Tectosilicatesmentioning
confidence: 99%
“…[25] Zudem wurden hochkondensierte, dreidimensionale Hochdruckmodifikationen von SrSiN 2 und BaSiN 2 anhand von Dichtefunktionalrechnungen vorhergesagt. [59] Das Oxonitridosilicat CaSi 2 O 2 N 2 hat eine unerwartete Struktur. Gemäß der empirischen Formel und dem entsprechenden Kondensationsgrad von k = 1 = 2 würde man eine dreidimensionale Gerüststruktur aus eckenverknüpften [SiX 4 ]-Tetraedern (X = O, N) erwarten.…”
Section: D-nitridosilicateunclassified
“…The search for compounds with similar compositions and structures in the data base gave no consistence and a trial of indexing with the program STOE WinXPOW [48] was not successful. As well the crystal structures of the predicted HP-phases of Römer et al [38][39][40] did not match with the observed reflections of the new phase.…”
Section: Structure Determination and Refinementmentioning
confidence: 90%
“…DFT‐calculation by Römer et al concerning novel high‐pressure phases of the MSiN 2 ‐compounds (M = Ca, Sr, Ba) predicted two new HP‐modifications for CaSiN 2 (β‐CaSiN 2 at 1.6 GPa with CaGeN 2 ‐structure type and γ‐CaSiN 2 at 60 GPa with LiFeO 2 ‐structure type), which has led to intense investigations of the HP‐behavior of the MSiN 2 ‐compounds (M = Mg, Ca, Sr, Ba) . In this contribution the new form HP‐ CaSiN 2 is reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation